The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
DOI: 10.11606/d.6.2014.tde-04092014-094314
|View full text |Cite
|
Sign up to set email alerts
|

Uso de serviços segundo a posse de plano privado de saúde  no município de São Paulo

Abstract: Introdução -O sistema de saúde brasileiro é composto por um segmento público universal e por um segmento privado. Grande parte da população do município de São Paulo está coberta por planos privado de saúde, porém existem poucos estudos locais explorando a influência desse fator no uso dos serviços de saúde. O estudo de unidades geográficas menores permite um melhor entendimento da realidade local. Objetivo -Analisar o uso dos serviços de saúde segundo a posse de plano privado de saúde no município de São Paul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Authors have published these studies between 1999 and 2017 (median: 2009) 5,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37 (Table 1). The authors of five studies reported having no conflicts of interest 19,28,31,33,35 , while in the other studies the authors did not disclose whether they had any conflicts of interest, nor did they examine interviewers' biases (in qualitative studies).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Authors have published these studies between 1999 and 2017 (median: 2009) 5,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37 (Table 1). The authors of five studies reported having no conflicts of interest 19,28,31,33,35 , while in the other studies the authors did not disclose whether they had any conflicts of interest, nor did they examine interviewers' biases (in qualitative studies).…”
Section: Resultsmentioning
confidence: 99%
“…While some studies had national coverage 5,12,13,14,22,24,25 , others covered certain geographical regions (e.g., Northeast or Southeast) 8,11,15,20,26 , states 16,33 , metropolitan areas 9,17,18 , municipalities 10,19,21,23,27,28,30,31,34,35,36,37 or parts of a municipality 22,32 . The study population included varied age groups, but most of them showed a balanced gender composition, with the exception of one study about men's health 37 and two about women's health 19,31 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations